Introduction to multimedia - Solomon, Ana Weston (Glencoe McGraw-Hill, 2006)
Glencoe’s Introduction to Multimedia is an essential classroom resource that enables students to understand the fundamentals of multimedia and provides hands-on practice with multimedia tools and skills. This complete guide describes types of multimedia productions, how multimedia affects society, and the components and tools that are used to produce a multimedia product. Independent and collaborative exercises promote an interactive learning environment within a project-based framework. Team projects provide students with practical experience of how a multimedia program comes together – from discussing project goals and varying team-member rolls, to how to organize and create a project from start to finish.